Rethingking of Talent Identification and Development (TID) Program in Indonesia - Gita Febria Friskawati (UNIB Press, 2022)
The last few decades have seen significant changes in trends related to athlete development, particularly in Talent Identification and Development (TID). The idea of talent continues to play an important role in most athlete development models, especially in Indonesia which aligns with the Great Design of National Sports (DBON). In this theoretical study, the authors highlight concerns with the notion of talent and how it is conceptualized in Indonesia's national sports system. First, the assumption that talent is a fixed capacity that can be identified early for children; second, the importance of ongoing research for the determination of TID; third, consideration of the multivariate TID approach. These concerns form the basis for more focused discussions on avenues and solutions for TID in Indonesia in the future.